Manejo De Miedo, Estrategias De Afrontamiento Y Cultura Ciudadana Para Prevención De La Violencia - Valdez, Sarah Margarita Chávez; del Villar, Oscar Armando Esparza (European Scientific Journal, ESJ, 2018)
In this study, an intervention program was designed and evaluated. This paper focuses on identifying beliefs, perceptions, and negative attitudes in the group, in order to continue with the promotion of positive socialemotional coping and the reduction of social fear. This, however, would help to elevate the behaviors of citizen participation and to inhibit antisocial behaviors. A sample of 47 women and 5 men, a total of 52 students from 17 to 21 years, were trained by means of didactic skill of cases and training in conflict management for a period of 11 weeks in a weekend modality. A quasiexperiment was designed using repeated measures, pretest-interventionpostest, and a control group. As a result, an increase in culture and citizen participation was found in the treatment group after 44 hours of intervention. Qualitative data indicate findings regarding group cognitive relations, assertive coping strategies in conflicting social situations, ability to analyze negative feelings, and a decrease in antisocial behavior.